Nutrient Condition in the Microenvironment Determines Essential Metabolisms of CD8+ T Cells for Enhanced IFNγ Production by Metformin - Chao, Ruoyu; Nishida, Mikako; Yamashita, Nahoko; Tokumasu, Miho; Zhao, Weiyang; Kudo, Ikuru; Udono, Heiichiro (Frontiers in Immunology, 2022)
Metformin (Met), a first-line drug for type 2 diabetes, lowers blood glucose levels by suppressing gluconeogenesis in the liver, presumably through the liver kinase B1-dependent activation of AMP-activated protein kinase (AMPK) after inhibiting respiratory chain complex I. Met is also implicated as a drug to be repurposed for cancers; its mechanism is believed identical to that of gluconeogenesis inhibition. However, AMPK activation requires high Met concentrations at more than 1 mM, which are unachievable in vivo. The immune-mediated antitumor response might be the case in a low dose Met. Thus, we proposed activating or expanding tumor-infiltrating CD8+ T cells (CD8TILs) in a mouse model by orally administering Met in free drinking water. Here we showed that Met, at around 10 μM and a physiologically relevant concentration, enhanced production of IFNγ,TNFα and expression of CD25 of CD8+ T cells upon TCR stimulation. Under a glucose-rich condition, glycolysis was exclusively involved in enhancing IFNγ production. Under a low-glucose condition, fatty acid oxidation or autophagy-dependent glutaminolysis, or both, was also involved. Moreover, phosphoenolpyruvate carboxykinase 1 (PCK1), converting oxaloacetate to phosphoenolpyruvate, became essential. Importantly, the enhanced IFNγ production was blocked by a mitochondrial ROS scavenger and not by an inhibitor of AMPK. In addition, IFNγ production by CD8TILs relied on pyruvate translocation to the mitochondria and PCK1. Our results revealed a direct effect of Met on IFNγ production of CD8+ T cells that was dependent on differential metabolic pathways and determined by nutrient conditions in the microenvironment.